2015
DOI: 10.4172/2379-1764.1000130
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Epicondylitis Injection Therapy: A Safety and Efficacy Analysis of Hyaluronate versus Corticosteroid Injections

Abstract: Lateral epicondylitis or tennis elbow, is a common elbow malady the extensor carpi radialis brevis origin. It is commonly treated by local injections of steroids are often associated with severe side effects and limited long term efficacy. Recently, hyaluronate is being increasingly used for the treatment of different degenerative processes of joints and soft tissue. Hyaluronate significantly and dose-dependently inhibits cell proliferation and decreased the expression level of mRNA for adhesion-related pro-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Some observations also support its use in a clinical environment to diminish pain and improve function (17,18). Moreover, some tests with patients suffering from various tendinopathies have demonstrated that HA injections can lead to better clinical results than with corticosteroid injections (19)(20)(21). We aimed to compare the effect of PRP versus HA injections after three months on patients who have a proximal patellar tendinopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Some observations also support its use in a clinical environment to diminish pain and improve function (17,18). Moreover, some tests with patients suffering from various tendinopathies have demonstrated that HA injections can lead to better clinical results than with corticosteroid injections (19)(20)(21). We aimed to compare the effect of PRP versus HA injections after three months on patients who have a proximal patellar tendinopathy.…”
Section: Introductionmentioning
confidence: 99%